Down‐regulation of miR‐10a‐5p in synoviocytes contributes to TBX5‐controlled joint inflammation. Issue 1 (7th August 2017) - Hussain, Nazim; Zhu, Wenhua; Jiang, Congshan; Xu, Jing; Wu, Xiaoying; Geng, Manman; Hussain, Safdar; Cai, Yongsong; Xu, Ke; Xu, Peng; Han, Yan; Sun, Jian; et al.
Abstract: MicroRNAs are considered to play critical roles in the pathogenesis of human inflammatory arthritis, including rheumatoid arthritis (RA). The purpose of this study was to determine the relationship between miR‐10a‐5p and TBX5 in synoviocytes and evaluate their contribution to joint inflammation. The expression of miR‐10a‐5p and TBX5 in the synovium of RA and human synovial sarcoma cell line SW982 stimulated by IL‐1β was determined by RT‐qPCR and Western blotting. The direct interaction between miR‐10a‐5p and TBX5 3′UTR was determined by dual‐luciferase reporter assay in HeLa cells. Mimics and inhibitors of miR‐10a‐5p were transfected into SW982 cells. TBX5 was overexpressed by plasmid transfection or knocked down by RNAi. Proinflammatory cytokines and TLR3 and MMP13 expressions were determined by RT‐qPCR and Western blotting. Down‐regulated expression of miR‐10a‐5p and up‐regulation of TBX5 in human patients with RA were found compared to patients with OA. IL‐1β could reduce miR‐10a‐5p and increase TBX5 expression in SW982 cells in vitro . The direct target relationship between miR‐10a‐5p and 3′UTR of TBX5 was confirmed by luciferase reporter assay. Alterations of miR‐10‐5p after transfection with its mimic and inhibitor caused the related depression and re‐expression of TBX5 and inflammatory factors in SW982 cells. Overexpression of TBX5 after pCMV3‐TBX5 plasmid transfection significantly promoted the production of TLR3, MMP13 and various inflammatory cytokines, while this effect was rescued after knocking down of TBX5 with its specific siRNA. We conclude that miR‐10a‐5p in a relation with TBX5 regulates joint inflammation in arthritis, which would serve as a diagnostic and therapeutic target for RA treatment.